Recent Developments on Noble Metal Based Microparticles for Their Applications in Organic Catalysis - Liu, Jian-Long; Jiang, Bo; Han, Guo-Zhi (Current Organic Chemistry, 2020)
Noble metal microparticles have been employed as desired catalysts for a number of classical organic chemical reactions due to their unique physicochemical properties. Currently, in order to obtain more benefits for practical applications such as low cost, easy separation and high selectivity, many efforts of scientists are devoted to constructing composite microparticles in which noble metals are coupled with other materials. In this paper, we summarize some recent research developments on noble metal based microparticles for their catalytic applications in organic synthesis. Among them, application of the gold and silver based microparticles is the focus of this paper for their relatively low cost and the diversity of preparation methods. Furthermore, the challenges and prospects of noble metal based microparticles for their applications in organic catalysis are also discussed.
Keywords: review